O01 Drug-related hospital admissions in paediatrics – what is preventable?. Issue 6 (17th May 2019) - Toni, I; Wimmer, S; Trollmann, R; Rascher, W; Neubert, A
Abstract : Background: Safety of paediatric pharmacotherapy is of major concern. Due to high off-label use (about 46–64% of patients in primary care are affected), missing paediatric dosage forms and complex dosage calculations, adverse drug reactions (ADR) and medication errors (ME) occur more often in children. 1–3 Moreover, it is estimated that 3 to 5% of paediatric hospital admissions are drug-related. 3–7 The aim of the present study was to systematically investigate the nature and preventability of drug-related hospital admissions in paediatrics. Methods: An observational study was carried out for 10 months at the Department of Paediatrics and Adolescent Medicine Erlangen, Germany. All patients aged 0 to <18 years, admitted during the study period and treated for at least 24 hours at the general paediatric ward were assessed and analysed with regard to ADR and ME requiring hospitalisation. The identification of these was based on intensive chart review. Seriousness was assessed using the ICH E2A criteria. 8 Results: 741 patients fulfilled the inclusion criteria and were screened for ADR and ME leading to hospital admission. Median age of patients was 7 years (IQR 1 – 13) while duration of stay was 2 days (IQR 2 – 4) at median level. In total 50 events were discovered in relationship to drug intake before hospitalisation; 41 (82.0%) of these were assessed with the seriousness criterion 'requires inpatient hospitalisation', while 23 (56.1%) events were preventable and therefore considered as ME. The incidence of drug-related hospital admissions was 5.5%. Conclusions: This study confirms that drug-related hospital admissions pose a significant problem in children and adolescents, however more than 50% of them were considered preventable. Increasing awareness towards paediatric pharmacotherapy and providing standardised guidance may help to reduce the risk for drug-related hospital admissions. References: Kimland E, Odlind V. Off-label drug use in pediatric patients. Clin Pharmacol Ther 2012;91:796–801. Wong IC, Ghaleb MA, Franklin BD, Barber N. Incidence and nature of dosing errors in paediatric medications: a systematic review. Drug Saf 2004;27:661–70. Smyth RM, Gargon E, Kirkham J, et al. Adverse drug reactions in children—a systematic review. PLoS One 2012;7:e24061. Rashed AN, Wong IC, Cranswick N, Tomlin S, Rascher W, Neubert A. Risk factors associated with adverse drug reactions in hospitalised children: international multicentre study. Eur J Clin Pharmacol 2012;68:801–10. Smyth RL, Peak M, Turner MA, et al. ADRIC: Adverse drug reactions in children—a programme of research using mixed methods. Programme Grants Appl Res 2014;2. Gallagher RM, Mason JR, Bird KA, et al. Adverse drug reactions causing admission to a paediatric hospital. PLoS One 2012;7:e50127. Neubert A, Dormann H, Weiss J, Criegee-Rieck M, Ackermann A, Levy M, Brune K, Rascher W. Are computerised monitoring systems of value to improve pharmacovigilance in paediatric patients? Eur J Clin Pharmacol 2006;62:959–65. ICH Expert Working Group. Clinical Safety Data Management: Definitions and Standards for Expedited Reporting E2A. 1994. Disclosure(s): Nothing to disclose.